Investigation of the airway management practice of emergency department ward nurses: a nationwide survey in China - Mei He; Juan Deng; Sufang Huang; Dengxiu Zou; Weiquan Liu; Jie Xiong (BMJ Open)
Objectives To investigate the airway management equipment and clinical practice in emergency department wards in China, and to explore the factors that influenced the nurses’ airway management practice.Design Cross-sectional study.Setting A nationwide survey covering the seven administrative regions of China (North China, Northeast China, East China, Central China, South China, Southwest China and Northwest China).Participants The nurses had to be registered nurses who worked in adult emergency department wards of the selected hospitals.Measures An online survey was designed, piloted and distributed to the members of the Emergency Medicine Committee of the Chinese Nursing Association, and the nurses from the members’ hospitals were invited to participate. The questionnaire was used to determine nurses’ clinical practice scores of airway management in emergency wards.Results Finally, we collected 995 valid questionnaires from 31 provinces and 143 districts in China. Among them, 361 (36.28%) nurses responded that their departments used open suction system (OSS) in clinical work, the major barrier for closed suction system (CSS) reported by 630 respondents (63.32%) was cost. Significant differences in all three scores were found in age, nursing experience years, technical title, airway management training experience and nursing specialist (all p<0.05). Correlations were found among airway management attitude, practice of sputum aspiration and practice of ventilator care bundles (r=0.655, r=0.543 and r=0.763, all p<0.001).Conclusions Chinese emergency department managers need to identify better methods for assessing equipment availability in OSS. CSS can be a choice when costs, status of the individual patient and severity of disease are comprehensively considered. Emergency department nurses’ scores of airway management practice were affected by demographic and job-related characteristics; regular training should be encouraged, and equipment and resources should be guaranteed to improve airway management quality and optimise patient outcomes.